2020
DOI: 10.1107/s2053230x20014880
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of barley agmatine coumaroyltransferase, an N-acyltransferase from the BAHD superfamily

Abstract: The enzymes of the BAHD superfamily, a large group of acyl-CoA-dependent acyltransferases in plants, are involved in the biosynthesis of diverse secondary metabolites. While the structures of several O-acyltransferases from the BAHD superfamily, such as hydroxycinnamoyl-CoA shikimate hydroxycinnamoyl transferase, have been elucidated, no structural information on N-acyltransferases is available. Hordeum vulgare agmatine coumaroyltransferase (HvACT) is an N-acyltransferase from the BAHD superfamily and is one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Nonetheless, the lack of comprehensive information regarding this branch has limited our exploration. Moreover, we observed that transferases with similar doughnut structures, such as BAHD superfamily enzymes (PDBID: 5KJS, 7CYS, 7W26, 8DQO,), possess comparable loop cover structures, suggesting that they may perform analogous functions in catalysis. Therefore, further research on such loop cover structures is crucial to comprehend the impact of intrinsic disordered loops on catalysis and to rationally design enzymes.…”
Section: Discussionmentioning
confidence: 93%
“…Nonetheless, the lack of comprehensive information regarding this branch has limited our exploration. Moreover, we observed that transferases with similar doughnut structures, such as BAHD superfamily enzymes (PDBID: 5KJS, 7CYS, 7W26, 8DQO,), possess comparable loop cover structures, suggesting that they may perform analogous functions in catalysis. Therefore, further research on such loop cover structures is crucial to comprehend the impact of intrinsic disordered loops on catalysis and to rationally design enzymes.…”
Section: Discussionmentioning
confidence: 93%
“…The protein structure models of MlAT6 were generated using the AlphaFold2 online server [34]. The molecular model revealed that MlAT6 possessed an active pocket located at the intersection of two pseudosymmetrical domains, consistent with the characteristic features of BAHD acyltransferases [35][36][37]. Subsequently, virtual docking experiments were performed to dock a p-coumaroyl-4'-hydroxyphenyllactate molecule and a p-coumaroyl shikimate molecule into the active cavity of MlAT6.…”
Section: Homology Modelling Revealed That Mlat6 Shares Multiple Activ...mentioning
confidence: 93%
“…The first characterized crystal structure of N-acyltransferase (refers to the acyltransferases using nitrogenous metabolites as substrates) in the BAHD family was of Hordeum vulgare agmatine coumaroyltransferase ( Hv ACT) (PDB ID: 7CYS). The structure shares some commonality with Rs VS, that is, they both consist of two domains connected by a long and large crossover loop, but the Hv ACT contains 18 β-strands (β1–β18) and 13 α-helixes (α1–α13) ( Yamane et al., 2020 ) ( Figure 2B ). The crystal structures of BAHD members have been published one after another, and the number of described structures is currently 26 ( Garvey et al., 2008 ; Garvey et al., 2009 ; Lallemand et al., 2012 ; Manjasetty et al., 2012 ; Walker et al., 2013 ; Eudes et al., 2016b ; Levsh et al., 2016 ; Chiang et al., 2018 ).…”
Section: Characteristics Of Bahd Acyltransferasesmentioning
confidence: 99%
“…The structure of Rs VS is reproduced according to reference reported by Ma et al. (2005) , and the structure of is Hv ACT reproduced according to reference reported Yamane et al. (2020) .…”
Section: Characteristics Of Bahd Acyltransferasesmentioning
confidence: 99%
See 1 more Smart Citation